1961
DOI: 10.1111/j.1151-2916.1961.tb15373.x
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Phases in the System Al2O3–AlN

Abstract: 358 pp.; Ceram. Abstr., 9 181 689 (1930). * ( a ) M. H. Jellinek and I. Fankuchen, "X-Ray Diffraction Examination of Gamma Alumina," InJ. Eng. Chem.. 37 [2] 158-63 (1945); Cerum. Abstr., 24 [5] 101 (1945). ( b ) M. H. Jellinek and I. Fankuchen, "X-Ray Examination of Pure Alumina Gel," I d . Eng. Chem., 41 [lo] 2259-65 (1949);Cerum. Abstr., 1950, August, p. 172a.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1

Year Published

1963
1963
2006
2006

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(16 citation statements)
references
References 6 publications
0
15
1
Order By: Relevance
“…Zeta alumina is a cubic spinel at low temperatures identical in structure to Al 2 O 3 with 11.4% AlN dissolved in it. 1 Schwetz et al 26 showed that small Li 2 O additions stabilize ␥-AlON formation in early sintering work with AlN. In the present work, when LiF or Li 2 O was substituted for LiAl 5 O 8 , at the same Li/Al ratio in the reaction sintering process, low temperature stabilization did not occur.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Zeta alumina is a cubic spinel at low temperatures identical in structure to Al 2 O 3 with 11.4% AlN dissolved in it. 1 Schwetz et al 26 showed that small Li 2 O additions stabilize ␥-AlON formation in early sintering work with AlN. In the present work, when LiF or Li 2 O was substituted for LiAl 5 O 8 , at the same Li/Al ratio in the reaction sintering process, low temperature stabilization did not occur.…”
Section: Discussioncontrasting
confidence: 63%
“…1 McCauley 2 showed that what has come to be known to many as AlON (i.e., 5AlN·9Al 2 O 3 ) can be modeled with a constant anion model. The spinel cation vacancies decrease as the nitrogen content increases.…”
Section: Introductionmentioning
confidence: 99%
“…cussed further by Long & Foster (1961). The powder data for (5-A1203 have recently been indexed on the basis of a large tetragonal cell containing sixteen molecules, but its detailed structure is unknown (Rooksby & Rooymans, 1961).…”
Section: Introductionmentioning
confidence: 99%
“…The AIN-AI20 3 system has been studied extensively in the last twenty years (Adams, AuCoin & Wolf, 1962;Collongues, Gilles, Lejus, Perez y Jorba & Michel, 1967;Gauckler, Lukas & Petzow, 1975;Gauckler & Petzow, 1977;Gilles, 1965;Jack, 1976;Lefebvre, 1975;Lejus, 1962Lejus, , 1964Long & Foster, 1961;Michel, 1972;Michel & Huber, 1970;Sakai, 1978;Slack, 1973;Yamaguchi & Yanagida, 1959). Phases in the system can be conveniently described by a parameter z defined by: 3zAIN + (1 -z)Al20 3 ~ mltz+2) N3zO(3_3z).…”
Section: Introductionmentioning
confidence: 99%
“…(b) This work; Gauckler et al (1975);Jack (1976);Sakai (1978). (c) Adams et al (1962); Collongues et al (1967); Gilles (1965); Lejus (1962Lejus ( , 1964; Long & Foster (1961);Michel (1972); Yamaguchi & Yanagida (1959). (d) Adams et al (1962); Collongues et al (1967); Gilles (1965); Lejus (1962Lejus ( , 1964; Michel (1972); Michel & Huber (1970); Lefebvre (1975).…”
Section: Introductionmentioning
confidence: 99%